Treatment of contaminated waters with non-essential and potentially toxic metals using biosorbents and zeolite materials - Fabre, Elaine (2019)
The growth of population and industrialization has dramatically reduced the water quality due to the release of diverse toxic metals into the aquatic bodies. Among these contaminants, mercury is considered one of the most hazardous because of its ability of accumulation in the living organisms and magnification along the food chain. Even at very low concentrations this metal persists in the environment and impacts ecosystems and human health. Governmental agencies like World Health Organization (WHO) and European Union (EU) have recognized the importance and urgency of remove this contaminant from waste waters. The Directive 2013/39/EU of the European Union classifies mercury as a priority substance that must be progressive eliminated of the emissions by 2021 and promotes the development of innovative cheaper technologies for its removal in water treatments. Despite the large number of works published in this subject, most of them report systems using unrealistic conditions such as high mercury concentrations and simple water matrices. There is still a big lack concerning the search and application of materials under environmental conditions with the aim to effectively offer an alternative to the conventional methods. In this sense, this study investigated the ability of various natural and synthetic sorbents to remove mainly mercury at low to moderate concentrations in spiked solutions. These two types of sorbents have advantages and their suitability to the process depend on the intended application. In the present study, tests were performed under laboratory-controlled conditions, using deionised water, tap water and seawater spiked from 50 µg dm-3 to 1000 µg dm-3 . In addition, a diluted effluent was also used to test the viability of the procedures under realistic conditions. The sorbents applied in the experiments were: AM-11, AM14, banana and potato peels, eggshells, Eucalyptus globulus barks, water hyacinth, coffee waste, Ulva intestinalis, Ulva lactuca, Fucus spiralis, Fucus vesiculosus, Gracilaria sp. and Osmundea pinnatifida. These sorbents were studied under several operating conditions simulating various contaminated waters, as those commonly reported in aquatic systems or industrial effluents. Among the sorbents tested, the synthetic materials presented higher capacities prospecting their potential for treating industrial effluents. Small doses as low as 14 mg dm-3 of AM-11 were able to remove more than 99 % of 1000 µg dm-3 of the mercury from spiked solutions. The capacities calculated from Langmuir isotherm for AM-11 and AM-14 were 161 and 304 mg g-1 , respectively. The use of biosorbents largely abundant in nature, such as agricultural or industrial wastes or marine macroalgae represent another promising alternative to conventional methods. In this context, banana peels, Ulva intestinalis, Ulva lactuca and Gracilaria sp. exhibited the best performances, being able to remove more than 98 % of Hg(II) from spiked seawaters with Hg(II) concentration of 50 µg dm-3 and to accomplish drinking water quality (i.e. Hg(II) concentration lower than 1 µg dm3 ). These biosorbents stood out for their faster kinetic (removing more than 80 % of Hg after 48 h of exposure), and ability to perform equally well in the presence of other competitive ions. In addition, these biosorbents have negligible costs offering excellent options for protecting water bodies.